PENGARUH PELATIHAN TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADAPT. PERKEBUNAN NUSANTARA III MEDAN - Salman Munthe; Reza Ichsan Nurul Ichsan (Jurnal Riset AKuntansi dan Bisnis)
This Study aimed to determine the impact of training on employee productivity. This research carried out in PT. Perkebunan Nusantara III located at Jln. Sei Batang Hari no. 2 Medan. This research uses quantitative methods by emphasizing the power analysis on the data processed by statistical methods. The selection of the sample is done by using probability sampling. The population of 100 employees were selected by random sampling technique, then 50 employees were chosen as the sample. The data collection instruments used were questionnaire. The Data were analyzed with the help of computer software statistical program for social sciences (SPSS) for windows release 20,0. Based on the findings calculated in SPSS 20,0, it can conclude that there is a significant influence of training on work productivity. Job training 76,5% impacted on employee productivity in PT. Perkebunan Nusantara III Medan.